The influence of the feed additive “Sylimevit” on the antioxidant protection of the body of dogs : ст. - Gutyj, B. V.; Petryshak, R. А. et. al.; Popadiuk, S. S.; Petryshak, O. І.; Martyshuk, T. V.; Oseredchuk, R. S.; Pryimych, V. I.; Naumyuk, О. S. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
Under the influence of the pathological factor, there is a change in the intensity of lipid peroxidation, the accumulation in the blood of the concentration of products of free radical oxidation and reactive oxygen species, a decrease in the buffer capacity of the blood relative to the maintenance of optimal parameters of the intensity of free extreme reactions. The work aimed to investigate the effect of the feed additive “Sylimevit” on the antioxidant protection of the body of dogs after preventive deworming. 10 German Shepherd dogs aged 1–2 years were used for experimental research. It was established that when feeding the feed additive “Sylimevit” to dogs in the period after deworming, activation of the enzyme link of the antioxidant system occurs in the blood, which is indicated by an increase in the activity of catalase and superoxide dismutase in the blood serum of these animals and inhibition of lipid peroxidation processes (reduction of secondary and end products lipid peroxidation). On the 30th day of the experiment, the activity of catalase and superoxide dismutase in the blood of animals of the experimental group was the highest, and the level of lipid peroxidation products was the lowest. The obtained research results confirm the antioxidant properties of the Sylimevit feed additive. This may be because the composition of the drug includes milk thistle, methiphene, and vitamins, which in turn enhance the effect of each other and thereby inhibit the formation of radicals and the processes of lipid peroxidation. It is also worth noting the antioxidant properties of milk thistle, which according to the literature, also have similar properties. The complex effect of the indicated biologically active elements provided high hepatoprotective and antioxidant effects.
Keywords: sylimevit; dogs; кормова добавка «Силімевіт»; корми для собак